2002
DOI: 10.1081/jlc-120014386
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Acetamiprid by HPLC-Fluorescence With Post-Column Photoderivatization and HPLC-Mass Selective Detection

Abstract: Two methods are described for determining the highly polar pesticide acetamiprid in vegetables. Residues are extracted with ethyl acetate and coextratives are removed with a graphitised Carbon-based packing ENVI-carb cartridge. Analysis is performed with goods results, by HPLC with post-column photoderivatization, and fluorescence detection and by HPLC-Electrospray ionisation mass spectrometry. The clean-up step is not necessary in this last case. LODs were 6 mg L À1 for HPLCfluorescence detection using matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…It was found that ATP exhibited high PIF signal intensity at λ ex /λ em = 257/382 nm, while its metabolite 6‐CNA shown the high PIF intensity at λ ex /λ em = 231/370 nm. These calculated wavelengths appeared approximately the same as previously reported [12,21]. Hence, the fluorescence detector was programmed at λ ex /λ em = 257/382 nm for ATP up to 6.0 min, while λ ex /λ em = 231/370 nm was set for 6‐CNA for the rest of the analysis time.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…It was found that ATP exhibited high PIF signal intensity at λ ex /λ em = 257/382 nm, while its metabolite 6‐CNA shown the high PIF intensity at λ ex /λ em = 231/370 nm. These calculated wavelengths appeared approximately the same as previously reported [12,21]. Hence, the fluorescence detector was programmed at λ ex /λ em = 257/382 nm for ATP up to 6.0 min, while λ ex /λ em = 231/370 nm was set for 6‐CNA for the rest of the analysis time.…”
Section: Resultssupporting
confidence: 62%
“…But its successful application is impeded by poor selectivity and sensitivity of UV detector for the accurate quantification of neonicotinoids in the sample matrices [6,7,12,19,20]. LC coupled with a fluorescence detector (LC‐FLD) is a comparatively simple, cost‐effective, sensitive, and selective technique for the high‐throughput and accurate quantification of analytes of interest [21]. Although, its direct application is restricted by the intrinsic nonfluorescent characteristic of neonicotinoids including ATP and its metabolite 6‐CNA.…”
Section: Introductionmentioning
confidence: 99%